The Effect of Ethambutol Therapy in terms of Visual Evoked Potential, Color Vision Test, and Contrast Sensitivity Test at the Subclinical Level: Oral Presentation - Observational Study - Resident - ARANDZ RUTTU; Dr. dr. Yunita, Sp.M(K), M.Kes; dr. Nurjannah Lihawa, Sp.P(K); dr. Muh. Firdaus Kasim, M.Sc; Dr. dr. Noro Waspodo, Sp.M(K); Dr. dr. Batari Todja Umar, Sp.M(K) (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Ethambutol is one of the first-line drugs in the treatment of tuberculosis and known to induce optic neuropathy. However, there are unknown protocols for detecting subclinical level of toxicity. The aim of this study was to assess the difference in amplitude and latency of visual evoked potential (VEP), color vision, and contrast sensitivity in tuberculosis patients before and after taking ethambutol for 1 and 2 months. Methods : This was a prospective observational cohort study of 38 eyes of 19 newly diagnosed patients with category-1 tuberculosis being treated with ethambutol. All patients were given ethambutol for 2 months at a dose of 15 - 20 mg/kg body weight/day. The participants underwent complete eye and visual function examination including pattern-reversal VEP, color vision with Farnsworth Munsell D-15 test, and contrast sensitivity with LEA Low Contrast Flip Chart before and after 1 and 2 months of treatment. Wilcoxon test was employed for data analysis. Results : During the study, no changes in visual acuity was observed. The results showed that the latencies of VEP after 1 month (p = 0.000) and 2 months (p = 0.000) of treatment were significantly delayed. There was a significant difference in contrast sensitivity after 2 months (p = 0.014) of treatment. However, no significant difference was found in color vision and amplitude of VEP. Conclusion : Latency of VEP and contrast sensitivity test could prove useful in detecting subclinical and hence very useful for monitoring patients under ethambutol therapy for ocular toxicity.